ANALYSIS OF THE EUROPEAN FUNDS ABSORPTION FOR RURAL DEVELOPMENT IN ROMANIA - Mihai, Dinu (Economics of Agriculture, 2011)
The paper studies the absorption of European funds and the payments made under The National Programme for Rural Development in Romania. Article begins with an introduction that refers to the importance of rural and European Common Agricultural Policy, the changes in the CAP related to rural development, it presents the differences between countries within the European Union and how these disparities can be reduced. It is a study of the four priority axes and measures included, as well as the value of public and private contributions allocated to Romania for the period 2007-2013. It is analyzed the progress in which it are payments for rural development in Romania for each axes and measures both numerical value and percentage reported to the total public contribution. Finally some conclusions on the progress results in which it is Romania regarding payments made for fnance projects submitted by the end of 2010. The results of this analysis can be used to form a clear image of access to European funds for rural development in Romania.